Worlds in Miniature Contemplating Miniaturisation in Global Material Culture - Davy, Jack; Dixon, Charlotte (UCL Press, 2019)
Miniaturisation is the creation of small objects that resemble larger ones, usually, but not always, for purposes different to those of the larger original object. Worlds in Miniature brings together researchers working across various regions, time periods and disciplines to explore the subject of miniaturisation as a material culture technique. It offers original contribution to the field of miniaturisation through its broad geographical scope, interdisciplinary approach, and deep understanding of miniatures and their diverse contexts. Beginning with an introduction by the editors, which offers one possible guide to studying and comparing miniatures, the following chapters include studies of miniature Neolithic stone circles on Exmoor, Ancient Egyptian miniature assemblages, miniaturisation under colonialism as practiced by the Makah People of Washington State, miniature surf boats from India, miniaturised contemporary tourist art of the Warao people of Venezuela, and dioramas on display in the Science Museum. Interspersing the chapters are interviews with miniature-makers, including two miniature boat-builders at the National Maritime Museum Cornwall and a freelance architectural model-maker. Professor Susanne Küchler concludes the volume with a theoretical study summarising the current state of miniaturisation as a research discipline. The interdisciplinary nature of the volume makes it suitable reading for anthropologists, archaeologists, historians and artists, and for researchers in related fields across the social sciences.